Acoustic percolation switches enable targeted drug delivery controlled by diagnostic ultrasound - Maria Paulene Abundo; Anna T. Tifrea; Marjorie T. Buss; Pierina Barturen-Larrea; Zhiyang Jin; Dina Malounda; Mikhail G. Shapiro (Proceedings of the National Academy of Sciences, 2025)
Delivering biomedicines to specific sites of disease using remote-controlled devices is a long-standing vision in biomedical research. However, most existing externally triggered delivery systems are based on complex micromachines that are controlled with electromagnetic waves and require custom external instrumentation. Here, we present a drug delivery platform based on a simple protein-containing hydrogel that can be both imaged and triggered to release drugs at specific locations using widely available diagnostic ultrasound devices. This technology is based on the addition of air-filled protein nanostructures called gas vesicles (GVs) to hydrogel delivery vehicles. While intact, GVs sterically block the release of drug payloads and allow the vehicle to be imaged with ultrasound. An increase in ultrasound pressure causes the collapse of GVs within the delivery vehicles at the desired anatomical location, instantly creating percolation channels in the hydrogel, massively increasing diffusivity, and leading to rapid drug release. Unlike previous ultrasound-actuated delivery approaches, both the imaging and release are performed using a simple diagnostic ultrasound probe ubiquitously available in clinical settings. We implement this concept by quantifying ultrasound-controlled drug diffusion and release in vitro and demonstrating image-guided protein delivery in vivo in the gastrointestinal (GI) tract following oral administration. We further validate this technology by using it to deliver anti-inflammatory antibodies to effectively treat a rat model of colitis. Targeted acoustic percolation switches (TAPS) open a conduit for local, image-guided drug delivery with a simple formulation and commonplace ultrasound equipment.